Development Strategy of Lanting Small Industry - Puspitasari, Atika Tri; Widiyanto, Widiyanto (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
This research aims to describe and analyze the strategy of production, marketing, human resources (labor), and capital. The technique of collecting data used observation, interviews, documentation, questionnaires, and triangulation. The technique of sampling was purposive sampling. Findings show that the strategy of production, marketing strategies by the way of increased order coupled with the trademark shows as well as various flavors of innovation development, adjustment of the selling price with the price of raw materials production, the cooperation of manufacturers and suppliers in the distribution of lanting, promotional activities by means of cooperation with the agency and related service trade off products online. The strategy of human resources is with the formation groups of industry in the village of Lemahduwur (but not running smoothly). Strategy capital with the initial capital comes from its own capital and profit as capital accumulation, additional capital when many party and by feast day; increased access to capital, financial administration and against accounting in a simple and routine. The advice given is the government and manufacturers improve HR, technology development, marketing and capital. Manufacturer improves collaboration with suppliers of raw materials, maintaining the typical features and making a trademark.